Molecular mobility and interactions in biopolymer-sugar-water systems - Farhat, Imad Akil (1996)
Since a significant range of food products may be regarded as biopolymer-sugar-water systems, questions relating to their production, structure and storage characteristics are of importance to the food industry. Information on molecular mobility and organization should provide genuine insight into such issues. The molecular properties of various biopolymer-sugar-water systems have therefore been studied using nuclear magnetic resonance (NMR) and Fourier transform infrared (FTIR) spectroscopies, and wide angle x-ray diffraction (WAXS). In general, the hydration of biopolymers in the water content range 0 to 1 g of water per g of dry matter, yielded an increase in the degree of order. 13C solid state NMR studies of xanthan powders showed an increasingly ordered structure at water contents exceeding 20% (dry weight basis) and a maximum degree of molecular organization above 75% water. This was supported by the results derived from FTIR and WAXS studies on the same material. Similar results were found in gelatin systems. The amide 1 band (-1660 cm'1) of the FTIR spectrum of the protein was deconvoluted into its individual components and the intensity of the components arising from ordered segments of the protein increased with hydration indicating a progressive ordering of the protein. The hydration of biopolymer-sugar mixtures was also investigated. Maize-sucrose (90:10 and 95:5) extrudates were studied using *H NMR relaxation as a function of moisture content; the results showed a 'quantum' increase in the mobility of the sugar at water contents between 15 and 20%. This was explained in terms of 'dissolution' of the sugar in the aqueous phase as a result of its increased preferential hydration. Further proofs of unequal partitioning of water during the hydration of biopolymer-sugar mixtures were obtained from an FTIR study of gelatin-sugar films. The intensity changes of the amide 1 band suggested a preferential hydration of the protein in the early stages of hydration, followed by a phase where the hydration of the sugar was favoured. On the basis of these experimental results, a model describing the process of hydration of biopolymer-sugar systems was proposed. In addition to the investigation of the rotational mobility of water in biopolymer and biopolymer-sugar systems, the translational mobility of water in such systems was also studied using pulsed field gradient NMR techniques. The self-diffusion coefficient of water in biopolymer gels showed a strong dependence on the diffusion time indicating the obstructive role of the polymer network. The diffusion coefficient of water was also reduced by increasing the concentration of the gel and the presence of sugar. Preliminary results obtained by comparing gels prepared by heating with those obtained by extrusion, suggested that the translational mobility of water was affected through modifications of the gel matrix. The rétrogradation of amylopectin-sugar (70:30 and 90:10) extrudates was studied adopting a molecular dynamics approach derived from glass-transition theory. While water enhanced exponentially the rate of rétrogradation, the effect of other plasticizers such as sugars was more complex. The rate results were regarded as a function of the offset of the storage temperature from the glass-transition temperature (T-Tg ).While fructose enhanced greatly the rate of amylopectin recrystallization, 30% xylose inhibited this reordering process. In contrast, sucrose increased the rate of retrogradation at low (T-Tg) (<60°C). The results suggested that sucrose could depress the rate constant at high (T-Tg). The impact of added sugar depended, therefore, on the sugar type and concentration in the system. The presence of the sugar in the system was found to affect the polymorphic form of the recrystallized amylopectin possibly implicating the sugar in the cell unit of the crystal. The rétrogradation kinetics were modelled using the Lauritzen-Hoffman theory employing the ten-Brinke equation to calculate Tg and the Flory equation to calculate the melting temperature (Tm). These calculations permitted the simulation of the joint effects of water content and storage temperature on the kinetics of the rétrogradation of amylopectin.